Gandhi and anarchy - Nair, Chettur Sankaran (New Delhi Pharos Books, 2022)
Gandhi And Anarchy This book is a result of an effort made by us towards making a contribution to the preservation and repair of original classic literature. In an attempt to preserve, improve and recreate the original content, we have worked towards: 1. Type-setting & Reformatting: The complete work has been re-designed via professional layout, formatting and type-setting tools to re-create the same edition with rich typography, graphics, high quality images, and table elements, giving our readers the feel of holding a 'fresh and newly' reprinted and/or revised edition, as opposed to other scanned & printed (Optical Character Recognition - OCR) reproductions. 2. Correction of imperfections: As the work was re-created from the scratch, therefore, it was vetted to rectify certain conventional norms with regard to typographical mistakes, hyphenations, punctuations, blurred images, missing content/pages, and/or other related subject matters, upon our consideration. Every attempt was made to rectify the imperfections related to omitted constructs in the original edition via other references. However, a few of such imperfections which could not be rectified due to intentional\unintentional omission of content in the original edition, were inherited and preserved from the original work to maintain the authenticity and construct, relevant to the work. We believe that this work holds historical, cultural and/or intellectual importance in the literary works community, therefore despite the oddities, we accounted the work for print as a part of our continuing effort towards preservation of literary work and our contribution towards the development of the society as a whole, driven by our beliefs. We are grateful to our readers for putting their faith in us and accepting our imperfections with regard to preservation of the historical content. HAPPY READING!
Keywords: Mahatma Gandhi; Philosophy; Indian Politics